The remaining obstacles for a totally implantable cochlear implant. Issue 5 (3rd August 2022) - Trudel, Mathieu; Morris, David P.
Abstract : Purpose of the review: For years, the development of a totally implantable cochlear implant (TICI) has faced several technical challenges hindering any prototypes from reaching full commercialization. This article aims to review the necessary specifications for a viable TICI. An overview of the remaining challenges when designing TICIs will be provided, focusing on energy supply and implantable microphones. Recent findings: The literature review highlights how research efforts to generate sufficient power to supply a fully implantable CI could take advantage of microelectromechanical systems (MEMS)-based energy harvesters incorporating piezoelectric materials. Using one of the various energy sources in the vicinity of the temporal bone would allow the development of a self-sufficient implant, overcoming the limitations of electrochemical batteries. Middle ear implantable microphones could also use similar fabrication techniques and transduction mechanisms to meet the sensor requirements for a TICI. Summary: Recent breakthroughs in power supply using MEMS-based energy harvesting technologies and piezoelectric implantable microphones may make TICIs become a more practical reality in the foreseeable future. Once available, TICIs will have major impact on our patients' quality of life and may help to make hearing rehabilitation a more appealing option to a greater proportion of those who fulfill our candidacy criteria.